O049 Sleep quality and its impact on children with primary ciliary dyskinesia. (7th October 2021) - Ewert, I; Robinson, P; Adams, A; Vandeleur, M
Abstract: Background: PCD is a rare, progressive disease resulting in upper respiratory manifestations and abnormal lung mechanics that increase one's risk of obstructive sleep apnoea. This study aims to characterise the sleep quality of children with PCD and its impacts on mood and HRQOL. Methods: Children with PCD aged 0–19 years with stable respiratory symptoms were recruited. Subjective sleep quality was assessed by the Sleep Disturbance Scale for Children (SDSC), OSA-18, and Paediatric Daytime Sleepiness Scale (PDSS). Mood and depressive symptoms were assessed via QOL-PCD and Children's Depressive Inventory (CDI) as age-appropriate. Pulmonary function testing was performed via spirometry and Multiple Breath Washout. Patients underwent an ENT assessment. All children completed one night of polysomnography including transcutaneous CO2 and video monitoring. Progress to date: Twenty participants (45% female) have been recruited with a mean age of 8.5 years. Mean (±SD) FEV1 is 76.5±22.9%. 73% of children assessed have chronic rhinosinusitis. Clinically significant scores for SDSC were observed in 79% of patients and in 30% of patients for OSA-18. 38% of children reported clinically significant scores for PDSS. To date, 7 children have completed polysomnography. Intended outcome and impact: This is the first study to characterise sleep quality and the impact of sleep disturbance in Australian children with PCD. We aim to identify clinical markers of poor sleep quality to better inform the development of a sleep screening program for use in paediatric PCD clinics.